2010
DOI: 10.3748/wjg.v16.i27.3394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fourBifidobacteriaon obesity in high-fat diet induced rats

Abstract: The response of energy metabolism to administration of Bifidobacteria is strain dependent. Different strains of Bifidobacteria might drive different directions of fat distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
164
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(179 citation statements)
references
References 32 publications
9
164
2
1
Order By: Relevance
“…The fermented burdock group had significantly higher cecal lactate (47.5 fold), acetate (2.7 fold), propionate (3.0 fold), butyrate (6.3 fold), and total organic acid (3.4 fold) Since Bifidobacterium consumption has been reported to reduce body fat in rodents, 33,34) the relationship between perirenal adipose tissue weight and cecal Bifidobacterium was analyzed. There was a significant inverse correlation between perirenal adipose tissue weight and cecal Bifidobacterium (r ¼ À0:515, p < 0:05), but cecal Bacteroides was not correlated with perirenal adipose tissue weight (r ¼ 0:421, p > 0:05).…”
Section: Resultsmentioning
confidence: 99%
“…The fermented burdock group had significantly higher cecal lactate (47.5 fold), acetate (2.7 fold), propionate (3.0 fold), butyrate (6.3 fold), and total organic acid (3.4 fold) Since Bifidobacterium consumption has been reported to reduce body fat in rodents, 33,34) the relationship between perirenal adipose tissue weight and cecal Bifidobacterium was analyzed. There was a significant inverse correlation between perirenal adipose tissue weight and cecal Bifidobacterium (r ¼ À0:515, p < 0:05), but cecal Bacteroides was not correlated with perirenal adipose tissue weight (r ¼ 0:421, p > 0:05).…”
Section: Resultsmentioning
confidence: 99%
“…53 In the case of probiotics interventions, not all but specific species and strains of bacteria demonstrate benefit. 51 Interventions with probiotics like Lactobacillus or Bifidobacterium species for 4-12 weeks have demonstrated significant improvements in body fat and insulin sensitivity. In addition, interventions with prebiotics like resistance starch, inulin, arabinoxylan demonstrated improvements in biomarkers associated with metabolic syndrome.…”
Section: Modulation Of Gut Microbiota By Dietary Interventionmentioning
confidence: 99%
“…A recent study has demonstrated that different types of bifidobacterial feeding resulted in either a decrease in both TG and cholesterol concentrations, or only in the TG concentration, in the serum of rats (23). Additionally, it has been reported that many strains of bifidobacteria have a cholesterol-lowering effect (24).…”
Section: Discussionmentioning
confidence: 99%